A large gastric inflammatory fibroid polyp revealed by an upper gastrointestinal bleeding: a case report - Ghada Gharbi; Manel Yakoubi; Asma Ben Mohamed; Moufida Mahmoudi; Mohamed Karim M’Farrej; Mahdi Bouassida; Amal Khsiba; Mouna Medhioub; Emna Chelbi; Lamine Hamzaoui (Future Science OA)
Inflammatory fibroid polyps (IFPs) are rare submucosal lesions that usually arise in the stomach. It represents 0.1% of all gastric polypoid lesions and are frequently asymptomatic. It’s usually revealed by an abdominal pain. Gastrointestinal bleeding can occur when the polyp is ulcerated. We report a case of a 72-year-old female with an IFP of the prepyloric region. The head of the polyp was thirty-five millimeters in diameter. It was revealed by an upper gastrointestinal bleeding and epigastric pain. An endoscopic resection was performed.